The importance of social others in cultural identification - Chew, Pony Yuen Ga (2016)
This research examines the roles that social relationships play in cultural identification – the knowledge and relational roles. We also proposed two complementary paths for individuals to develop a strong cultural identification – the knowledge path and the relational path. The knowledge path refers to the conventional understanding of cultural identification as involving the alignment of an individual’s self and the culture on important and widely shared values and beliefs. The relational path requires the existence of close social others who form a relational link connecting the individual to the culture. Four studies were conducted to demonstrate the importance of social others in cultural identification, and to refine the conceptual understanding and processes underlying both knowledge and relational paths of cultural identification, especially in the fulfilment of path-specific psychological needs.